2020
DOI: 10.3390/foods9040471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rearing System on the Straight and Branched Fatty Acids of Goat Milk and Meat of Suckling Kids

Abstract: Goat meat is considered healthy because it has fewer calories and fat than meat from other traditional meat species. It is also rich in branched chain fatty acids that have health advantages when consumed. We studied the effects of maternal milk and milk replacers fed to suckling kids of four breeds on the straight and branched fatty acid compositions of their muscle. In addition, the proximal and fatty acid compositions of colostrum and milk were studied. Goat colostrum had more protein and fat and less lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
(73 reference statements)
3
8
0
Order By: Relevance
“…The milk of Saanen goats had more iC17:0, C17:1n9, and less C21:0 and C20:1n9 than the milk of Saanen x Anglo-Nubian crossbreds. In general, the most abundant FA in the milk of all goat breeds was C10:0, C12:0, C14:0, C16:0, and C18:1n9, which is consistent with the findings of other researchers (Ripoll et al, 2020;Lopez et al, 2019).…”
Section: The Influence Of Crossbreeding On Goat Milk Yield Compositio...supporting
confidence: 91%
“…The milk of Saanen goats had more iC17:0, C17:1n9, and less C21:0 and C20:1n9 than the milk of Saanen x Anglo-Nubian crossbreds. In general, the most abundant FA in the milk of all goat breeds was C10:0, C12:0, C14:0, C16:0, and C18:1n9, which is consistent with the findings of other researchers (Ripoll et al, 2020;Lopez et al, 2019).…”
Section: The Influence Of Crossbreeding On Goat Milk Yield Compositio...supporting
confidence: 91%
“…In addition, the feeding regime of the goats determines the fat content of the milk that the kids consume [ 26 , 52 ], modifying, in turn, the fat profile of the kids’ meat [ 57 ] since they do not hydrogenate them in the rumen. Thus, it is logical to believe that dams from CM and TMR kids, with diets rich in linoleic acid and linolenic acid, have milk with a higher content of polyunsaturated fatty acids that would pass to the adipose tissue [ 26 , 58 ] of their kids, making their fat more susceptible to oxidation [ 59 ] and therefore with higher MDA values.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies by our team on other Spanish goat breeds have shown that different carcass and meat quality traits improved when animals were fed natural milk, although some interactions between breed and rearing system were found [ 10 , 12 , 13 , 14 , 15 ]; consequently, further analysis is necessary. The aim of this work was to study the influence of the use of milk replacers on several carcass characteristics of suckling kids from several Spanish goat breeds.…”
Section: Introductionmentioning
confidence: 99%